PTEN at the crossroad of metabolic diseases and cancer in the liver - Manlio Vinciguerra; Michelangelo Foti (Annals of Hepatology, 2008)
The tumor suppressor PTEN is a phosphoinositide phosphatase regulating the PI3K/Akt signaling pathways and mutated or deleted in a variety of human cancers. Recent evidence indicates that dysregulated PTEN expression and activity in the liver critically affect hepatic insulin sensitivity and trigger the development of non-alcoholic fatty liver diseases. As well, PTEN expression/activity is also affected with HBV and HCV infection, or following alcohol-related injury. Finally, PTEN mutations/deletions or low PTEN expression are associated with diverse liver malignancies thus suggesting a critical role for PTEN in hepatic cancers. This review will focus on our current knowledge of the regulation of PTEN expression/activity and the role of this phosphatase in liver diseases.